SCREENING FOR DEMENTIA: IS 1 SIMPLE QUESTION THE ANSWER?. Issue 11 (14th October 2015) - Aji, Baba; Larner, Andrew
Abstract : Objective: To examine the diagnostic utility of the dementia screening question from the DoH Dementia CQUIN document (2012) in consecutive patients in a dedicated epilepsy clinic, individuals in whom memory complaints are common. Results: 100 consecutive outpatients (M:F=61:39, median age 44.5 years) were asked 'Have you been more forgetful in the past 12 months to the extent that it has significantly affected your life?', as advocated in the Dementia CQUIN document. There was a 48% yes response. No patient was adjudged to have dementia. Comparing the yes/no groups, there was no difference in sex ratio, age, seizure type, or use of antiepileptic drugs (monotherapy versus polytherapy). Those answering yes were more likely to be follow-up than new patients. Intergroup difference in epilepsy duration showed a trend to longer duration in the yes group. The most common examples of memory problems volunteered were forgetting to attend appointments, take medications, or switch off appliances, suggestive of attentional rather than mnestic problems. Conclusions: These data suggest that the Dementia CQUIN screening question has very low specificity, and hence will identify many false positives, with risk of overdiagnosis of dementia in individuals with purely subjective memory impairment.